Ordinance to Regulate the Carrying of Pistols, reprinted in BROOKLYN DAILY EAGLE Brooklyn Daily Eagle, Oct. 26, 1880, at 1 - (:unkn) unknown (My University, 1880)
Prohibited concealed carry of any pistol without a license. Licenses only issued to individuals twenty-one and over in age.
Keywords: CARRY - CONCEALED